2013
DOI: 10.3354/meps10015
|View full text |Cite
|
Sign up to set email alerts
|

Competitive hierarchies among three species of juvenile coral reef fishes

Abstract: Interspecific competition is often asymmetric, and it can limit the spatial distributions of competitively inferior species within a community. When asymmetric competition involves 2 or more component species, the ranking of species' competitive abilities may form competitive hierarchies (all species of higher rank out-compete all species of lower rank) or competitive networks (at least 1 species of lower rank out-competes ≥1 species of higher rank). Expectations of resource monopolization and patterns of dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…A range of mechanisms have been proposed to explain coexistence of superior and inferior competitors, including competition colonisation trade-offs (Tilman 1994), the intermediate disturbance hypothesis (Connell 1978;Sousa 1979), microhabitat partitioning (Denno, Mcclure & Ott 1995) and complex behaviours generating the formation of hierarchies among species (e.g. Geange, Adrian & Jeffrey 2013). One behavioural mechanism by which individuals compete over limiting resources and generate such species hierarchies is via aggressive contests (Smith & Price 1973;Austad 1989).…”
Section: Introductionmentioning
confidence: 99%
“…A range of mechanisms have been proposed to explain coexistence of superior and inferior competitors, including competition colonisation trade-offs (Tilman 1994), the intermediate disturbance hypothesis (Connell 1978;Sousa 1979), microhabitat partitioning (Denno, Mcclure & Ott 1995) and complex behaviours generating the formation of hierarchies among species (e.g. Geange, Adrian & Jeffrey 2013). One behavioural mechanism by which individuals compete over limiting resources and generate such species hierarchies is via aggressive contests (Smith & Price 1973;Austad 1989).…”
Section: Introductionmentioning
confidence: 99%
“…As each facultative cleaner wrasse in our study overlaps in habitat with other Thalassoma (in addition to other wrasses), juveniles of each of these species compete for prey directly with saturated assemblages of adult conspecifics and congeners. Geange et al (Geange et al, 2013) show that even among juvenile non-cleaner taxa in this clade, intense asymmetric competition between congeners can arise within areas of high density. Our results suggest that cleaning behavior may present a mechanism by which such competition is reduced by providing juvenile facultative cleaner species an alternate source of prey.…”
Section: Why Clean?mentioning
confidence: 99%
“…We suggest that these reduced suites of mechanical features -low maxillary KT, small gape and low bite force -in Thalassoma wrasses may have evolved as a result of competitive displacement. Thalassoma wrasses co-occur, often in great abundance, in many tropical regions including but not limited to the Indian Ocean, the Indo-Pacific and the Caribbean (Randall et al, 1997;Geange, 2010;Geange et al, 2013;Froese and Pauly, 2014). In fact, field surveys conducted in the Indo-Pacific and Caribbean found that reef crests were typically numerically dominated by members of this clade (Bellwood et al, 2002).…”
Section: Why Clean?mentioning
confidence: 99%
“…Larvae may be able to delay maturation to avoid settling during brighter periods of the lunar cycle and/or target predictably darker periods (Shima et al 2018) when the effectiveness of nocturnal reef-based predators may be curtailed (Acosta and Butler 1999). Postsettlement mortality of young sixbars is strongly density dependent (Shima 2001b, Shima andOsenberg 2003), and is further mediated by priority effects (Geange and Stier 2009), as well as by interactions with other species (Shima 2001a, Shima et al 2006, 2008, Geange et al 2013.…”
Section: Study Systemmentioning
confidence: 99%